Love Gifts - Ojaide, Tanure, 1948- (Book collections on Project MUSE., 2013)
This book is a love sequence: the poetic rendering of the relationship between the minstrel and his muse over a long period. The poet uses the relationship of the two personages to investigate the human condition; hence the poems deal with dreams, desires, frustrations, hopes, contentment, and seeking meaning in life. The poetic canvas links the two figures to other relationships and happenings of their time in an all-embracing manner. In a way, minstrel and muse, lovers, are in these "songs" sharing a unique relationship with readers as they affirm their humanity and tell the complicated passage they navigate hourly and daily as members of a particular society